2019
DOI: 10.3390/ijerph16244999
|View full text |Cite
|
Sign up to set email alerts
|

A Soluble Humic Substance for the Simultaneous Removal of Cadmium and Arsenic from Contaminated Soils

Abstract: With abundant oxygen-containing functional groups, a humic substance (HS) has a high potential to remediate soils contaminated by heavy metals. Here, HS was first extracted from a leonardite and analyzed for its chemical compositions and spectroscopic characteristics. Then it was assessed for its ability as a washing agent to remove Cd and As from three types of soils (red soil, black soil, and fluvo-aquic soil) that were spiked with those contaminants (Cd: 40.5–49.1 mg/kg; As: 451–584 mg/kg). The operational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 42 publications
1
10
0
2
Order By: Relevance
“…Very Soil organic matter (SOM) is one of the main factors controlling the physical, chemical, and biological properties of soil and plays an important role in soil hygiene (immobilization of heavy metals and organic pollutants) [46]. Recent research has unequivocally confirmed the key role of organic carbon in the sorption of inorganic and organic contaminants [47], and the presence of organic substances can inhibit metal absorption from soil solution and reduce metal mobility and bioavailability [43,48,49]. In the study area, SOM values ranged from 1.4 to 9.8%, indicating that the soil humus supply is moderate to very good.…”
Section: Degree Of Contamination (C D )mentioning
confidence: 99%
“…Very Soil organic matter (SOM) is one of the main factors controlling the physical, chemical, and biological properties of soil and plays an important role in soil hygiene (immobilization of heavy metals and organic pollutants) [46]. Recent research has unequivocally confirmed the key role of organic carbon in the sorption of inorganic and organic contaminants [47], and the presence of organic substances can inhibit metal absorption from soil solution and reduce metal mobility and bioavailability [43,48,49]. In the study area, SOM values ranged from 1.4 to 9.8%, indicating that the soil humus supply is moderate to very good.…”
Section: Degree Of Contamination (C D )mentioning
confidence: 99%
“…The pH value of HSs was close to neutral, positively influencing the removal rate and limiting the possible destructive effect on the soil. The high removal efficiency of Cd and As from soils and the low content of other metals (Cd: 0.09, Pb: 5.32, Cu: 8.72, Cr: 6.60, As: 3.69, Ni: 8.39, Zn: 20.36 mg/kg) confirm the applicability of using HSs for the remediation of contaminated soil (Bi et. al., 2019).…”
Section: Remediation Of Soils Contaminated With Heavy Metals -Cadmium and Arsenicmentioning
confidence: 78%
“…It is important to adjust the washing conditions to the soil properties. Important factors are the pH value, the duration and cycles of washing and the HSs concentration (Bi, Yuan, Wei, Xiao, Feng, Meng and Wang, 2019). The content of Cd and As in soil can be a serious problem in specific places, as is the case in China.…”
Section: Remediation Of Soils Contaminated With Heavy Metals -Cadmium and Arsenicmentioning
confidence: 99%
See 2 more Smart Citations